Analysis Of Inhibiting Factors Of Agility Of Women's Msmes In Makassar City - Karmilah Karmilah; Ahmad Farhan; Al Kausar (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to examine the key barriers faced by female-owned Small and Medium Enterprises (SMEs) in Makassar City, focusing on financial access, education and training opportunities, and social-cultural factors. Using factor analysis, data were collected from female entrepreneurs across various subdistricts in Makassar. The results highlight that access to financial resources, such as loans and venture capital, and participation in business networks are the most significant challenges faced by these women. Additionally, issues related to household responsibilities and limited access to quality education and training programs further hinder the agility of female-owned SMEs. The study also identifies that financial constraints, particularly high loan costs and difficulties in obtaining funding approvals, are the primary obstacles. While participation in education programs plays a moderate role, social factors like unequal household work distribution also impact business success. However, the research is limited by its focus on a single geographic area, reliance on self-reported data, and a cross-sectional design, which may not capture the full complexity of challenges faced by female entrepreneurs over time. The findings suggest that policy interventions should prioritize improving access to financial resources and business networks, enhancing educational opportunities, and addressing gender-related social barriers to support the growth of female-owned SMEs in Makassar City